2022
DOI: 10.3390/sports10060086
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Vertical Jump Performance and Ankle Joint Range of Motion: Effect of Knee Joint Angle and Handedness in Young Adult Handball Players

Abstract: The purpose of the study is to examine the effect of the ankle joint range of motion (ROM) on the vertical jump (VJ) performance of adult handball players. The active (ACT) and passive (PAS) ankle joint ROM of 12 male members of the U21 National Handball Team with the knee joint at 0°, 40°, and 90° flexion (0° = fully extended knee) was evaluated using a video analysis measuring method. Participants also performed maximum VJ with (CMJ) and without (SQJ) countermovement, as well as with (AS) and without (NAS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…This assumption could be further supported by the notion that the higher the force accelerating the ankle motion, the greater the ankle range of motion [ 56 ]. Previous research in handball players revealed that laterality, based on hand preference, resulted in significant differences in the active ankle joint range of motion at the selected knee angle where the flexibility test in the present study was conducted [ 57 ]. Additionally, a recent study applying a stretching protocol to 1 leg for 12 weeks reported increases in the ankle range of motion of the non-trained leg, a finding that led the researchers speculate that volleyball training, per se, probably affects ankle flexibility [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…This assumption could be further supported by the notion that the higher the force accelerating the ankle motion, the greater the ankle range of motion [ 56 ]. Previous research in handball players revealed that laterality, based on hand preference, resulted in significant differences in the active ankle joint range of motion at the selected knee angle where the flexibility test in the present study was conducted [ 57 ]. Additionally, a recent study applying a stretching protocol to 1 leg for 12 weeks reported increases in the ankle range of motion of the non-trained leg, a finding that led the researchers speculate that volleyball training, per se, probably affects ankle flexibility [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first-time derivative of the recorded vertical GRF defined RFD, while P MAX was the peak value of the multiplication product of the vertical GRF by the vertical CoM velocity during the propulsive phase [ 17 ]. Based on h JUMP , the following vertical jump performance parameters were also calculated [ 35 , 36 ]: SSC gain (Equation (1)): …”
Section: Methodsmentioning
confidence: 99%
“…In another study, it was suggested that achieving a full ROM can improve the maximal sprint speed of team athletes [9]. Empirical evidence demonstrated a strong correlation between lower limb ROM and vertical jump performance among elite handball players [10].…”
Section: Introductionmentioning
confidence: 99%